2002
DOI: 10.1253/circj.66.715
|View full text |Cite
|
Sign up to set email alerts
|

Esmolol Protects the Myocardium and Facilitates Direct Version Intracardiac Operation With a Beating Heart

Abstract: irect version intracardiac surgery on the beating heart is a newly developed technique that does not use aortic cross-clamping or hypothermic cardiac arrest. 1,2 The nearly normal physiological conditions enables continuous coronary artery blood supply and overcomes the deficiencies of traditional methods. However, operating on the beating heart increases the difficulty of maneuvering and sometimes excessive tugging is inevitable. 3 Beta-1-blockers, which have been successfully used in heart disease, not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…It has been used in a number of clinical situations in which rapid reversal of effect may be necessary, including during acute myocardial ischemia and during cardiopulmonary bypass surgery. 25,26 Esmolol was chosen in this study because its period of action was similar to the duration of the catecholamine surge measured by tissue microdialysis after prolonged VF and resuscitation. We did see a blunting of the maximum systolic arterial blood pressure after ROSC, showing that esmolol did moderate the functional effects of the catecholamine surge.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in a number of clinical situations in which rapid reversal of effect may be necessary, including during acute myocardial ischemia and during cardiopulmonary bypass surgery. 25,26 Esmolol was chosen in this study because its period of action was similar to the duration of the catecholamine surge measured by tissue microdialysis after prolonged VF and resuscitation. We did see a blunting of the maximum systolic arterial blood pressure after ROSC, showing that esmolol did moderate the functional effects of the catecholamine surge.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al (28) reported that in a direct vision of an intracardiac beating-heart surgery, esmolol protects the myocardium and facilitates the operation, as demonstrated by the maintenance of the myocardial ultrastructure. In addition, Scorsin et al (29) measured the transmyocardial gradient of the oxygen content and revealed that esmolol provides potent myocardial protection in hypertrophied hearts, at least partly, by reducing the myocardial oxygen metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…По сообщению авторов, эсмолол при внутривенном введении эффективно и обратимо снижал частоту сердечных сокращений и диастолическое артериальное давление без каких бы то ни было серьезных неблагоприятных воздействий [13]. В другом рандомизированном плацебо-контролируемом исследовании было показано, что ранняя терапия внутривенными бета-адреноблокаторами достоверно уменьшает размеры инфаркта миокарда [14].…”
Section: Lecture лекцияunclassified